2017
DOI: 10.1136/bjsports-2016-097372.137
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Biomechanics and Jump Performance in Healthy and Chronic Ankle Instability Individuals During Landing: A Triple Blind Randomized Clinical Trial of Ankle Taping Efficacy

Abstract: BackgroundClinicians regularly utilize ankle taping procedures to prevent ankle sprains during practice/competition. Though many different ankle taping applications are employed, the effect of these on biomechanics and performance is unknown.ObjectiveTo investigate changes in ankle biomechanics during landing and jump performance with ankle taping.DesignTriple-blind randomized.SettingUniversity laboratory.ParticipantsTwenty-eight participants (14 healthy, 14 with chronic ankle instability [CAI]).InterventionsE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The biomechanical performance analysis methods for the single-swing and triple-swing rope skipping include the literature review method, expert interview method [8], and experimental method. The literature review method mainly refers to reviewing the relevant literature about rope skipping and the application of biomechanics in sports activities to understand the relationship between rope skipping and biomechanics.…”
Section: Experimental Contentmentioning
confidence: 99%
“…The biomechanical performance analysis methods for the single-swing and triple-swing rope skipping include the literature review method, expert interview method [8], and experimental method. The literature review method mainly refers to reviewing the relevant literature about rope skipping and the application of biomechanics in sports activities to understand the relationship between rope skipping and biomechanics.…”
Section: Experimental Contentmentioning
confidence: 99%
“…Most studies have observed the ankle biomechanics and kinetics during landing from a drop jump, 12,13 and showed the use of the nonelastic closed-basket weave taping technique for the prevention strategies of an inversion ankle sprain. Taping can increase kinesthetic awareness and limit the range of motion at the ankle joint, reducing inversion motion.…”
Section: Introductionmentioning
confidence: 99%